Dariusz Koźbiał, Status prawny zawodu tłumacza przysięgłego, seria Monografie Prawnicze, Wydawnictwo C.H. Beck, Warszawa 2024, ss. 232, ISBN: 978–83–8356–414–2 - Jachimowicz-Jankowska, Paulina (Studia Prawa Publicznego, 2024)
Dariusz Koźbiał, Status prawny zawodu tłumacza przysięgłego, seria Monografie Prawnicze, Wydawnictwo C.H. Beck, Warszawa 2024, ss. 232, ISBN: 978–83–8356–414–2 (opr. Paulina Jachimowicz-Jankowska).